এমাজউদ্দীন আহমদ সংবর্ধনা গ্রন্থ - শিকদার, আবদুল হাই; বড়ুয়া, সুকোমল; নাজনীন, দিল রওশন জিন্নাত আরা; পারভেজ, মাহফুজ
Articles on the life and works of Emajuddin Ahamed, educator and professor from Bangladesh; commemorative volume.